Effects of Hole Etching Depth in a Long Wavelength InGaAsP Photonic Crystal Vertical Cavity Surface Emitting Laser - Marjani, Saeid; Marjani, Hamid (Asian Journal of Chemistry, 2012)
In the present work, we presented the effects of the hole etching depth on various elements of heat sources within the active region of a long-wavelength InGaAsP photonic crystal vertical cavity surface emitting laser. The device employs InGaAsP active region, which is sandwiched between GaAs/AlGaAs and GaAs/AlAs distributed Bragg reflectors (DBRs). This paper provides key results of the various elements of heat sources upon the hole etching depth, including the Joule heat power, the recombination heat power and the Thomson heat power.